Numerical Simulation of Hot Dry Rock Fracture Monitoring by Time-Lapse Magnetotelluric Method - Lige Bai; Jing Li; Zhaofa Zeng (Energies, 2022)
The spatial distribution of rock fractures during water injection in hot dry rock (HDR) geothermal is essential information for evaluating geothermal well fracturing. The rock fractures produce anisotropic electrical characteristics, which may facilitate geophysical methods for monitoring fracture distribution. This paper studies the anisotropic magnetotelluric (MT) response in water injection fracturing based on the finite difference method (FEM). It uses the residual phase tensor (PT) method to calculate the characteristics of fracture strike and dip angle. The feasibility analysis of the technique under a different angle and resistivity conditions in geothermal reservoir investigation is discussed in detail. The results demonstrate that the MT can explain the characteristics of anisotropic resistivity structure changes from the water injection fracturing of HDR at the 5 km depth. The time-lapse MT monitoring method can provide a reliable scientific basis for fracture distribution direction and spreading characteristics.